Ending hunger by 2050: crucial investments and policies - Runge, C. Ford; Senauer, Benjamin; Pardey, Philip G.; Rosegrant, Mark W. (International Food Policy Research Institute, 2003)
To end hunger and prevent the recurrence of famine and starvation, we need to take the following steps: invest in public health, child nutrition, education, women’s and girls’ social status, and other components of human capital; reform public institutions and create innovative funding and partnership arrangements; change government policies at all levels to be both pro-poor and pro-growth; increase funding for scientific and technological research to boost agricultural production and efficiency; and develop specific policies and institutions to deal with environmental degradation caused by population growth. The international community, national governments, nongovernmental organizations (NGOs), and the private sector must cooperate to bring about these changes, which reach beyond redistribution programs, narrowly focused market-oriented solutions, or campaigns based solely on local self-reliance. -- from text